Maternal age, social changes, and pregnancy outcome in Ribeirão Preto, southeast Brazil, in 1978-79 and 1994 Idade materna, mudanças sociais e prognóstico da gestação em Ribeirão Preto, Sudeste do Brasil, entre 1978-79 e 1994 - Marcelo Zubaran Goldani; Heloisa Bettiol; Marco Antonio Barbieri; Andrew Tomkins (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2000)
This study focused on changes in demographic, social, and health-care patterns and pregnancy outcome related to maternal age from 1978-79 to 1994 in Ribeirão Preto, São Paulo State, Brazil. Information on pregnancy outcome was obtained from two cohorts of singleton live births, 6,681 births in 1978/79 and 2,839 births in 1994. A standardized questionnaire was submitted to mothers after delivery, and demographic information was collected from official records. There was a significant increase in teenage pregnancies (from 5.1% to 7.4%) and a decrease in infant mortality (36/1,000 to 17/1,000). There were significant decreases in the proportion of mothers with low schooling (24.5% to 14.4%), smoking (28.9% to 21.%), and multiparity (14.7% to 9.0%). Prenatal coverage improved (from 23.4% to 9.0% of patients with fewer than 4 prenatal visits), while cesareans increased (from 30.6% to 50.8%), as did preterm delivery (7.2% to 13.6%) and low birthweight (7.2% to 10.6%). Despite significant improvements in some maternal characteristics, the proportion of teenage pregnancies, preterm deliveries, low birthweight, and cesareans increased, raising concerns about the health costs and consequences for mothers and infants. Foram estudadas as mudanças nos padrões demográficos, sociais e de atenção à saúde e prognóstico da gestação relacionados com a idade materna, entre 1978-79 e 1994, em Ribeirão Preto, São Paulo, Brasil. As informações sobre a gestação foram obtidas de duas coortes de recém-nascidos vivos de parto único hospitalar, 6.681 nascimentos em 1978/79 e 2.839 em 1994. Um questionário padronizado foi aplicado às mães após o parto e informações demográficas foram coletadas de fontes oficiais. Houve aumento significante da gravidez na adolescência (5,1% para 7,4%) e decréscimo na mortalidade infantil (36/1.000 para 17/1.000). Ocorreu diminuição na proporção de mães com baixo nível educacional (24,5% para 14,4%), fumantes (28,9% para 21,0%) e multíparos (14,7% para 9,0%). Houve melhora na cobertura do pré-natal (23,4% para 9,0%, com menos de 4 consultas) e aumento de parto cesáreo (30,6% para 50,8%), de parto pré-termo (7,2% para 13,6%) e de baixo peso ao nascer (7,2% para 10,6%). Apesar das melhorias, elevou-se a proporção de mães adolescentes, partos pré-termo, baixo peso ao nascer e cesarianas, trazendo preocupação quanto ao custo para a saúde e às conseqüências para mães e crianças.